(untitled) (European Journal of Health Research, 2020)
The use of transcatheter aortic valves replacement (TAVR) has increased due to the aging and high risk population. Some reports have shown promising results on their hemodynamic performance with adequate morbidity and mortality rates. However, the impact of these bioprostheses on left ventricular mass (LVM) is unknown. The main objective of our study was to analyze LVM regression and ventricular remodeling with theses bioprostheses in real-world patients after TAVR. From January 2010 to December 2011, 61 patients underwent transcatheter aortic valve replacement due to severe aortic stenosis.The demographic and clinical characteristics and hemodynamic, electrocardiographic and echocardiographic parameters were collected and analysed. The results are: we observed statistically significant differences between the preoperative and postoperative values in the electrocardiographic parameters, expressed by the criteria of SokolowLyon, Cornell and their respective duration-voltage products, the size of the interventricular septum showed a decrease of 14mm to 11mm and the indexed ventricular mass showed a decrease expressed in terms of the magnitude of the difference of up to 30 g / m2, that is, it has been reduced from 145.5 g / m2 to 115 g / m2. The conclusions are: ventricular remodeling is favorable in TAVR groups measured by echocardiography and electrical criteria, improving contractility and event-free survival at one year follow-up